Method for testing thermal mechanical fatigue crack propagation of metal material
Through the thermal mechanical fatigue crack propagation test method of metal materials, finite element analysis and improved flexibility method are used to solve the problem of inconsistent test results in the existing technology, and the accurate evaluation of metal materials under complex thermal mechanical fatigue conditions is achieved. Provides a safe and economical design basis for high-temperature structures.
Patent Information
- Application Number
- CN202411367933.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art lacks a unified test method to study the crack propagation behavior of metal materials under complex thermal mechanical fatigue conditions, resulting in inconsistent test results, affecting the safety and economics of high-temperature structures.
A metal material thermal mechanical fatigue crack propagation test method is adopted, through finite element analysis, optical measurement and improved flexibility method, the variable temperature alternating load conditions are simulated, and the crack propagation rate and plastic zone evolution are calculated in real time to ensure the test results. unity and reliability.
This method can accurately simulate the complex working conditions of high-temperature components, improve the stability and repeatability of test results, provide a solid theoretical basis for the damage tolerance design and safe verification of high-temperature structures, extend the service life of the equipment and reduce maintenance costs.
Smart Images

Figure CN119246268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material mechanical property testing, and in particular relates to a crack extension testing method for metal materials under complex thermal-mechanical coupling loading conditions. Background Art
[0002] In the aerospace, electric power, energy and other industrial fields, many hot-end components face the combined effects of severe temperature changes and cyclic mechanical loads during service, namely thermomechanical fatigue. Long-term loading of thermomechanical fatigue can lead to fracture failure of key components, which has become an important reason affecting the integrity of high-temperature structures, causing serious safety hazards and economic losses. In addition, due to the limitations of detection methods and production economic considerations, many components already have tiny cracks during the processing and manufacturing stage or in the early stages of service. These cracks will accelerate under the action of thermomechanical fatigue loads, causing premature failure of the workpiece.
[0003] At present, there are relatively few studies on the thermomechanical fatigue crack growth behavior of metal materials, and due to the lack of a unified test method, different operators use the same material and the same loading conditions to test, but get significantly different or even completely opposite test results. Therefore, there is an urgent need for a unified and effective metal material thermomechanical fatigue crack growth test method to measure the crack growth behavior of metal materials under complex thermomechanical loading conditions, so as to provide the test data necessary for equipment damage tolerance design and safety verification. Summary of the invention
[0004] The present invention proposes a method for testing the thermomechanical fatigue crack growth of metal materials, which is aimed at evaluating the thermomechanical fatigue crack growth behavior of metal materials under extreme service environments, filling the technical gap in this field. The present invention can effectively simulate the working conditions of variable temperature and alternating load coupling that high-temperature components are subjected to during service, and obtain the specific crack growth rate and the evolution of the plastic zone in the crack growth area, which is conducive to researchers' in-depth discussion of the thermomechanical fatigue crack growth mechanism of metal materials, and at the same time helps to ensure the uniformity of test results, and provides important test data and theoretical basis for the damage tolerance design and safety verification of high-temperature structures under harsh working conditions.
[0005] The above-mentioned object of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for testing the thermomechanical fatigue crack growth of a metal material, comprising the following steps:
[0007] S1: According to the size of the metal sample, the functional relationship between the crack length a and the sample flexibility Ev / P under constant temperature conditions, as well as the functional relationship between the crack extension driving force ΔK and the crack length a are obtained by the finite element method;
[0008] Moreover, natural surface speckles are formed on the surface of the metal specimen;
[0009] S2: Prefabricate cracks using the constant load method at room temperature;
[0010] S3: Measure the length of the crack before the test by optical method, and mark the relative test machine clamping position and high temperature extensometer installation position on the metal specimen;
[0011] S4: Install the metal sample and the high temperature extensometer on the testing machine; determine whether the test is a variable temperature test, if yes, jump to step S5, otherwise jump to step S6;
[0012] S5: Measure the temperature-thermal strain relationship of metal specimens;
[0013] S6: Set the loading parameters of the testing machine, including stress amplitude, stress ratio, stress waveform, temperature amplitude, temperature mean, temperature waveform, cycle period, and mechanical-temperature load phase angle;
[0014] S7: starting a thermomechanical fatigue crack growth test, during which a surface natural speckle image of the crack growth area is collected in real time, and real-time image distortion correction is performed; when the crack length reaches a predetermined length as monitored by the surface natural speckle image collected in real time, the test is stopped to obtain a test result;
[0015] S8: Determine whether the test is a variable temperature test, if yes, jump to step S9, otherwise jump to step S10;
[0016] S9: Based on the temperature-thermal strain relationship obtained in S5, thermal strain compensation is performed on the test results obtained in S7 to obtain mechanical strain;
[0017] S10: The crack length corresponding to each cycle of the metal sample is calculated by the improved compliance method, and the crack growth rate is calculated by combining the functional relationship between the crack growth driving force ΔK and the crack length a obtained in S1;
[0018] The calculation process of the improved flexibility method is as follows:
[0019] S101: using the test results to calculate stress data, thereby obtaining a mechanical strain-stress hysteresis loop, and intercepting a linear portion of an unloading segment in each cycle of the mechanical strain-stress hysteresis loop in the test;
[0020] S102: Calculate the mean of each of the four adjacent data points in the linear part. The elastic modulus of the metal sample at different temperatures is measured in advance. The modulus is converted using the average temperature of each of the four adjacent data points to obtain the elastic modulus E of the metal sample per unit time. i ; Use the mechanical strain of adjacent data points to subtract and obtain the deformation v of the metal sample per unit time i; then a mechanical strain-stress curve of n points can be carried out n-3 times E i *v i Calculate; where i is the calculation order;
[0021] S103: Select the stress difference between point 1 and point n-3 as P, and obtain the compliance result ∑E under thermomechanical fatigue loading i v i / P;
[0022] S104: Substitute the flexibility result into the relationship between the crack length a and the flexibility Ev / P of the metal sample obtained in S1 to obtain the crack length.
[0023] Furthermore, in S1, P is the stress difference of the metal sample, v is the deformation of the metal sample, and E is the elastic modulus of the metal material.
[0024] Furthermore, in S1, the natural speckle on the surface is obtained by slow wire cutting.
[0025] Furthermore, in S2, the allowable upper limit of the prefabricated load used in the constant load method is: the yield strength of the metal specimen at room temperature multiplied by λ and then multiplied by 80%; wherein λ is the ratio of the stress amplitude in S6 divided by the yield strength corresponding to the highest temperature set for the test in S7.
[0026] Furthermore, S3 also includes measuring the length of the crack before the test by an optical method.
[0027] Furthermore, in S4, if an induction coil is used to heat the metal sample, it is necessary to ensure that the axial temperature gradient of the induction coil in the metal sample is less than 10°C.
[0028] Further, in S5, the mechanical loads at both ends of the metal sample are set to be kept at 0, and a cyclic temperature load is applied to the metal sample by an induction heating device, and the temperature-thermal strain data is measured and recorded by a high-temperature extensometer.
[0029] Furthermore, in S5, data of at least 20 temperature cycles are measured to obtain average results of temperature and thermal strain.
[0030] Further, in S7, the image of the natural speckle on the surface is collected by an image collection device.
[0031] Furthermore, in S7 and S9, the test results include time, total strain, mechanical load, and temperature.
[0032] Furthermore, in S9, the thermal strain compensation is to divide each cycle in the test data obtained in S7 into a heating section and a cooling section. For the heating section and the cooling section, the thermal strain data corresponding to the heating section and the cooling section in the temperature-thermal strain relationship are respectively subtracted from the total strain in the test results to obtain the mechanical strain.
[0033] Furthermore, S10 also includes using S7 to collect the natural speckle image of the surface, and calculating the plastic zone and strain field at the crack tip by digital image correlation technology.
[0034] Furthermore, in S10, the crack extension driving force ΔK is calculated by the crack length a, and then the crack extension increment is obtained by subtracting the crack lengths a of adjacent cycles. The functional relationship between ΔK and the crack extension increment is the crack extension rate.
[0035] The beneficial effects of the present invention are:
[0036] The method of the present invention can accurately simulate the complex working conditions faced by high-temperature components during actual service, namely the dual coupling of alternating temperature and mechanical load, ensuring the high consistency between the test environment and the actual application scenario, and providing a more practical test platform for the performance evaluation of metal materials in harsh environments. Through a carefully designed test process and advanced monitoring technology, the method of the present invention can accurately obtain the crack growth rate and the evolution details of the plastic zone in the crack growth area. These data not only quantify the fatigue damage process of the material, but also provide detailed data support for in-depth research on the mechanism of thermomechanical fatigue crack growth. In view of the inconsistency of results that is common in similar tests in the past, the method of the present invention effectively improves the stability and repeatability of the test results by optimizing the test condition control, standardizing the operation process and introducing precision measurement technology, providing a more reliable test basis for scientific research and engineering applications, which not only helps researchers to deeply analyze the damage evolution mechanism of metal materials under thermomechanical fatigue, but also promotes the improvement and innovation of related theoretical models, and provides a solid theoretical basis for the optimization design, damage tolerance design and safety verification of high-temperature structural materials. In view of the wide application of high-temperature components in key fields such as aerospace, energy and power, petrochemicals, etc., this method is of great significance for improving the safety performance of equipment in these fields, extending its service life, and reducing maintenance costs, showing broad application prospects and social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of the present invention.
[0038] Figure 1The optical microscope images of (a) the natural speckle pattern on the surface and (b) the particle size in Example S1 of the present invention;
[0039] Figure 2 The effect of hot air flow on image distortion is analyzed by a quartz grid plate in Example S7 of the present invention: (a) room temperature, (b) 550°C, (c) during a temperature rise of 350 to 550°C, and (d) during a temperature drop of 350 to 550°C;
[0040] Figure 3 (a) the standard grid scale plate and (b) the captured image used in Example S7 of the present invention;
[0041] Figure 4 The effect comparison before and after distortion correction in Example S7 of the present invention is as follows: (a) before distortion correction, (b) after distortion correction;
[0042] Figure 5 The process and effect of thermal strain compensation in Example S9 of the present invention: (a) temperature-thermal strain data in the cooling section and the heating section, (b) the total strain-stress hysteresis loop obtained in the test, and (c) the mechanical strain-stress hysteresis loop obtained after thermal strain compensation. Figure 6 This is a comparison chart of the crack length result calculated by the improved compliance method in Example S10 of the present invention and the result of the traditional optical direct observation method. DETAILED DESCRIPTION
[0043] The present invention is further described below with reference to the accompanying drawings and specific embodiments, but the embodiments do not limit the present invention in any form.
[0044] This embodiment further illustrates the present invention by conducting a thermomechanical fatigue crack growth test on 316LN austenitic stainless steel.
[0045] S1: According to the size of the metal specimen, the functional relationship between the crack length a and the specimen flexibility Ev / P under constant temperature conditions, as well as the functional relationship between the crack extension driving force ΔK and the crack length a are obtained through finite element simulation.
[0046] Among them, P is the stress difference of the metal sample; v is the deformation of the metal sample; E is the elastic modulus of the metal material.
[0047] In this embodiment, the metal sample is cut by slow wire cutting to obtain natural speckles on the surface. The morphology of the natural speckles on the surface is similar to the particle size. Figure 1 The results of optical microscope photography show that the average size of natural speckles on the surface is 15 microns. The slow wire cutting method can effectively ensure that the speckles will not separate with the deformation of the metal material during the test.
[0048] S2: Prefabricate cracks using the constant load method at room temperature.
[0049] When the constant load method is used for crack prefabrication, the prefabrication load should be lower than 80% of the maximum mechanical load in the test. Since the yield strength of metal specimens at room temperature is much higher than that of high temperature tests, in order to improve the efficiency of crack prefabrication, the load can be set using the normalized result relative to the current yield strength. Specifically, the stress amplitude in S6 is divided by the yield strength corresponding to the highest temperature set in the test in S7 to obtain the ratio λ, and the yield strength of the metal specimen at room temperature is multiplied by λ and then multiplied by 80% to obtain the allowable upper limit of the prefabrication load.
[0050] In this embodiment, the yield strength of 316LN material is 135MPa at 550℃, and the yield strength at room temperature (25℃) is 280MPa. If the stress amplitude in the formal high temperature test is 120MPa, it is 88.89% of the corresponding yield strength; at this time, the crack prefabrication stress at room temperature should be lower than 80% of this value (88.89%), that is, lower than 71.11% of the corresponding yield strength at room temperature, and the specific value is lower than 199.11MPa. Therefore, the range of 0-150MPa is selected to load cyclically at a frequency of 2.5Hz until the prefabrication is stopped when the crack length reaches 1mm.
[0051] S3: Measure the crack length before the test by optical method, and mark the relative test machine clamping position and high temperature extensometer installation position on the metal specimen to reduce installation error.
[0052] S4: Install the metal specimen and the high temperature extensometer on the testing machine; determine whether the test is a variable temperature test, if yes, jump to step S5, otherwise jump to step S6.
[0053] If an induction coil is used to heat the metal sample, the coil distribution should be adjusted before the formal test to ensure that it does not affect the installation of the high-temperature extensometer and the image acquisition of the crack propagation area. At the same time, the temperature distribution in the induction coil in the metal sample should be tested in advance to ensure that the axial temperature gradient is less than 10°C to avoid affecting the accuracy of the test results.
[0054] S5: Measure the temperature-thermal strain relationship of the metal sample: Set the mechanical load at both ends of the metal sample to 0, and apply a cyclic temperature load to the metal sample through an induction heating device, and measure and record the temperature-thermal strain data through a high-temperature extensometer.
[0055] In order to reduce the influence of temperature distribution, at least 20 temperature cycles should be measured to obtain the average results of temperature and thermal strain.
[0056] S6: Set the loading parameters of the testing machine, including stress amplitude, stress ratio, stress waveform, temperature amplitude, temperature mean, temperature waveform, cycle period, and mechanical-temperature load phase angle.
[0057] In this embodiment, the stress amplitude is set to 120 MPa, the stress ratio is 0, the stress waveform is a triangular wave, the temperature amplitude is 100°C, the temperature average is 450°C, the temperature waveform is a triangular wave, the cycle period is 60 seconds to complete one cycle, and the mechanical-temperature load phase angle is 180°.
[0058] S7: Start the thermomechanical fatigue crack growth test. During the test, the natural speckle image of the surface of the crack growth area is collected in real time through the image acquisition equipment, and the real-time image distortion correction is performed. When the crack length reaches the predetermined length through the real-time collected natural speckle image of the surface, the test is stopped and the test results of time, total strain, mechanical load and temperature are obtained.
[0059] Among them, for image acquisition equipment, the acquisition deviation caused by factors such as high-temperature oxidation, hot air flow and high-temperature self-luminescence of metal samples during the speckle acquisition process should be considered and corrected.
[0060] Before the test, the metal sample was kept at the highest temperature in the test for 2 hours to fully oxidize the surface speckle and reduce the influence of the change of the oxidation degree of the metal sample surface on the image acquisition during the test. Using a quartz grid plate fixed on the surface of the metal sample, the image acquisition equipment measured the influence of factors such as hot air flow and high-temperature self-luminescence of the metal sample, such as Figure 2 As shown. Figure 2 It can be seen that under the influence of various temperature fields, the node distance of the quartz grid plate has not changed, which means that the image acquisition is not affected by factors such as hot air flow and high-temperature self-luminescence of the sample. If the distance between the grid nodes changes, the induction coil, heat dissipation equipment and image acquisition device should be adjusted.
[0061] In addition, the optical distortion of the image acquisition device should be considered and corrected to ensure the accuracy of image acquisition. Figure 3 As shown in the figure, the standard grid scale plate is photographed using an image acquisition device and distortion correction is performed. The distortion correction effect is shown in Figure 3 shown.
[0062] S8: Determine whether the test is a variable temperature test, if yes, jump to step S9, otherwise jump to step S10.
[0063] S9: According to the temperature-thermal strain relationship obtained in S5, thermal strain compensation is performed on the test results of time, total strain, mechanical load, and temperature obtained in S7 to obtain mechanical strain;
[0064] Specifically, Figure 5As shown in (a), the temperature-thermal strain data is divided into a heating part and a cooling part, and thermal strain compensation is performed on the heating part and the cooling part respectively. Each cycle in the test data obtained in S7 is divided into a heating section and a cooling section. For the heating section and the cooling section, the total strain in the test result is subtracted from the thermal strain data corresponding to the heating section and the cooling section in the temperature-thermal strain relationship to obtain the mechanical strain, as shown in Figure 5 As shown in (b)(c).
[0065] S10: Use S7 to collect the natural speckle image of the surface, and use the digital image correlation technology to calculate the plastic zone and strain field at the crack tip for post-test analysis. For the calculation part of the digital image correlation technology, the calculation parameters should be kept consistent to ensure the accuracy of the calculation results. Among them, the consistent calculation parameters refer to the consistent sub-area radius, sub-area span and calculation smoothness.
[0066] The crack length corresponding to each cycle of the metal sample is calculated by the improved compliance method, and the crack growth rate is calculated by combining the functional relationship between the crack growth driving force ΔK and the crack length a obtained by S1.
[0067] The improved flexibility method is based on the ASTM E647 standard and is suitable for calculating the crack length based on the change in flexibility of metal specimens under variable temperature conditions. The specific calculation process of the improved flexibility method is as follows:
[0068] S101: using the test results to calculate stress data, thereby obtaining a mechanical strain-stress hysteresis loop, and intercepting the linear part of the unloading section in each cycle of the mechanical strain-stress hysteresis loop in the test;
[0069] S102: Calculate the mean of each of the four adjacent data points in the linear part. The elastic modulus of the metal sample at different temperatures is measured in advance. The modulus is converted using the average temperature of each of the four adjacent data points to obtain the elastic modulus E of the metal sample per unit time. i ; Subtracting the mechanical strain of adjacent data points can obtain the deformation v of the metal sample per unit time i ; then a mechanical strain-stress curve of n points can be carried out n-3 times E i *v i Calculation; where i is the calculation order.
[0070] S103: Select the stress difference between point 1 and point n-3 as P, and obtain the compliance result ∑E under thermomechanical fatigue loading i v i / P.
[0071] S104: Substitute the flexibility result into the relationship between the crack length a and the flexibility Ev / P of the metal sample obtained in S1 to obtain the crack length.
[0072] Among them, the initial crack length obtained by the improved compliance method is compared with the initial crack length measured in S3 to verify the calculation accuracy.
[0073] Finally, the crack extension driving force ΔK is calculated by the crack length a, and the crack extension increment is obtained by subtracting the crack lengths a of adjacent cycles. The functional relationship between ΔK and the crack extension increment is the crack growth rate.
[0074] The crack length is directly measured by conventional optical observation method and compared with the crack length calculated in this embodiment. Figure 6 As shown, it can be seen that the crack lengths calculated under different test conditions are consistent with the crack lengths directly measured by the traditional optical observation method, which proves the accuracy of the crack length calculation of the present invention.
[0075] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.
Claims
1. A method for testing the thermal mechanical fatigue crack growth of a metal material, characterized in that: The steps include: S1: According to the size of the metal sample, the functional relationship between the crack length a and the sample flexibility Ev / P under constant temperature conditions, as well as the functional relationship between the crack extension driving force ΔK and the crack length a are obtained by the finite element method; Moreover, natural surface speckles are formed on the surface of the metal specimen; S2: Prefabricate cracks using the constant load method at room temperature; S3: Mark the relative test machine mounting position and high temperature extensometer installation position on the metal specimen; S4: Install the metal sample and the high temperature extensometer on the testing machine; determine whether the test is a variable temperature test, if yes, jump to step S5, otherwise jump to step S6; S5: Measure the temperature-thermal strain relationship of metal specimens; S6: Setting the loading parameters of the testing machine, including stress amplitude, stress ratio, stress waveform, temperature amplitude, temperature mean, temperature waveform, cycle period, and mechanical-temperature load phase angle; S7: starting a thermomechanical fatigue crack growth test, during which a surface natural speckle image of the crack growth area is collected in real time, and real-time image distortion correction is performed; when the crack length reaches a predetermined length as monitored by the surface natural speckle image collected in real time, the test is stopped to obtain a test result; S8: Determine whether the test is a variable temperature test, if yes, jump to step S9, otherwise jump to step S10; S9: Based on the temperature-thermal strain relationship obtained in S5, thermal strain compensation is performed on the test results obtained in S7 to obtain mechanical strain; S10: The crack length corresponding to each cycle of the metal sample is calculated by the improved compliance method, and the crack growth rate is calculated by combining the functional relationship between the crack growth driving force ΔK and the crack length a obtained in S1; The calculation process of the improved flexibility method is as follows: S101: using the test results to calculate stress data, thereby obtaining a mechanical strain-stress hysteresis loop, and intercepting a linear portion of an unloading segment in each cycle of the mechanical strain-stress hysteresis loop in the test; S102: Calculate the mean of each of the four adjacent data points in the linear part. The elastic modulus of the metal sample at different temperatures is measured in advance. The modulus is converted using the average temperature of each of the four adjacent data points to obtain the elastic modulus E of the metal sample per unit time. i ; Use the mechanical strain of adjacent data points to subtract and obtain the deformation v of the metal sample per unit time i ; then a mechanical strain-stress curve of n points can be carried out n-3 times E i *v i Calculate; where i is the calculation order; S103: Select the stress difference between point 1 and point n-3 as P, and obtain the compliance result ΣE under thermomechanical fatigue loading i v i / P; S104: Substitute the flexibility result into the relationship between the crack length a and the flexibility Ev / P of the metal sample obtained in S1 to obtain the crack length.
2. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: In S1, P is the stress difference of the metal sample, v is the deformation of the metal sample, and E is the elastic modulus of the metal material; in S1, the natural speckle on the surface is obtained by slow wire cutting.
3. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: In S2, the allowable upper limit of the prefabricated load used in the constant load method is: the yield strength of the metal sample at room temperature multiplied by λ and then multiplied by 80%; where λ is the ratio of the stress amplitude in S6 divided by the yield strength corresponding to the highest temperature set for the test in S7.
4. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: S3 also includes measuring the length of the crack before the test by an optical method.
5. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: In S4, if the metal sample is heated by an induction coil, it is necessary to ensure that the axial temperature gradient of the induction coil in the metal sample is less than 10°C.
6. A method for testing the thermomechanical fatigue crack growth of a metal material according to claim 1, characterized in that: In S5, the mechanical loads at both ends of the metal sample are set to remain at 0, and a cyclic temperature load is applied to the metal sample through an induction heating device, and the temperature-thermal strain data are measured and recorded through a high-temperature extensometer; in S5, at least 20 temperature cycle data are measured to take the average results of temperature and thermal strain respectively.
7. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: In S7, the image of the natural speckle on the surface is collected by an image collection device.
8. A method for testing the thermomechanical fatigue crack growth of a metal material according to claim 1, characterized in that: In S7 and S9, the test results include time, total strain, mechanical load, and temperature.
9. A method for testing the thermomechanical fatigue crack growth of metal materials according to claim 1, characterized in that: In S9, the thermal strain compensation is to divide each cycle of the test data obtained in S7 into a heating section and a cooling section. For the heating section and the cooling section, the thermal strain data corresponding to the heating section and the cooling section in the temperature-thermal strain relationship are respectively subtracted from the total strain in the test results to obtain the mechanical strain.
10. A method for testing the thermomechanical fatigue crack growth of a metal material according to claim 1, characterized in that: S10 also includes using S7 to collect the natural speckle image of the surface, and calculating the plastic zone and strain field at the crack tip through digital image correlation technology; in S10, the crack extension driving force ΔK is calculated by the crack length a, and then the crack length a of adjacent cycles is subtracted to obtain the crack extension increment. The functional relationship between ΔK and the crack extension increment is the crack extension rate.
Citation Information
Patent Citations
Creep crack propagation C* integral testing device and method
CN116990148A
Estimation method for fatigue crack growth rate of metal material under elastic-plastic condition
CN117954022A
Manufactured articles methods of making articles and of measuring article fatigue life
GB1466875A
Cited By
Thermal mechanical fatigue crack growth rate testing method based on rigidity and crack tip strain field
CN120706153A
Thermomechanical fatigue crack growth rate test method based on stiffness and crack tip strain field
CN120706153B
